La motivación y su incidencia en el desempeñolaboral de la empresa AYNI SAC – La Esperanza 2022 - Rodríguez Aramburú, Anghely Roxana (2022)
The main purpose of this study was to determine the impact of motivation on job performance in the company AYNI SAC - La Esperanza 2022, under a non experimental methodological design of correlational type and quantitative approach. to this end, the 35 workers of the company were considered as the universe according to their payroll, to whom two questionnaires were administered as instruments of data collection through the survey technique. In this regard, it was determined that both intrinsic and intrinsic motivation have a positive and direct impact (sig. = 0.000) on job performance, and it was also identified that productivity and goal achievement are the dimensions of job performance that have the greatest impact on the motivation of workers, concluding at a general level that motivation has a positive and direct impact (sig.= 0.000; r= 0.778) on job performance at AYNI SAC, so the more motivated AYNI employees are, the better their job performance will be.